Ordered nanostructures through colloidal self assembly - Koh, Yaw Koon (2008)
The fabrication of ordered nanostructures plays an important role in the realization of the potential of nanotechnology and consequently, it has become an intense field of research in recent years. One promising method of fabrication is the self assembly process of colloidal particles into ordered structures. The process is highly efficient but suffers from the drawback that defective structures form under most experimental conditions. This is due to the lack of understanding of the underlying mechanism. In this thesis, the process is investigated in order to help in the understanding. This is achieved by monitoring the structural changes in-situ during the process. The method of monitoring makes use of a property of the nanostructure known as the photonic bandgap. The bandgap is strongly dependent on the quality of the structure and can be monitored easily by simple optical methods. One important result of the experiments is the identification of a transition structure during the self assembly process. The driving force for the transition structure is the microscopic interaction forces between the particles in suspension. This observation highlights the inadequacies of previous studies where the driving force for colloidal self assembly is solely attributed to capillary forces. By combining both the interaction and capillary forces, the mechanism of self assembly is elucidated. With the new understanding, the origin of defects can be identified. Finally, conditions for growth of high quality nanostructures by colloidal self assembly are also identified.